Minimally invasive evacuation of spontaneous intracerebral hemorrhage using sonothrombolysis - Newell, David W. (2011)
OBJECT: Catheter-based evacuation is a novel surgical approach for the treatment of brain hemorrhage. The object of this study was to evaluate the safety and efficacy of ultrasound in combination with recombinant tissue plasminogen activator (rt-PA) delivered through a microcatheter directly into spontaneous intraventricular (IVH) or intracerebral (ICH) hemorrhage in humans. METHODS: Thirty-three patients presenting to the Swedish Medical Center in Seattle, Washington, with ICH and IVH were screened between November 21, 2008, and July 13, 2009, for entry into this study. Entry criteria included the spontaneous onset of intracranial hemorrhage ≥ 25 ml and/or IVH producing ventricular obstruction. Nine patients (6 males and 3 females, with an average age of 63 years [range 38–83 years]) who met the entry criteria consented to participate and were entered into the trial. A ventricular drainage catheter and an ultrasound microcatheter were stereotactically delivered together, directly into the IVH or ICH. Recombinant tissue plasminogen activator and 24 hours of continuous ultrasound were delivered to the clot. Gravity drainage was performed. In patients with IVHs, 3 mg of rt-PA was injected; in patients with intraparenchymal hemorrhages, 0.9 mg of rt-PA was injected. The rt-PA was delivered in 3 doses over 24 hours. RESULTS: All patients had significant volume reductions in the treated hemorrhage. The mean percentage volume reduction after 24 hours of therapy, as determined on CT and compared with pretreatment stability scans, was 59 ± 5% (mean ± SEM) for ICH and 45.1 ± 13% for IVH (1 patient with ICH was excluded from analysis because of catheter breakage). There were no intracranial infections and no significant episodes of rebleeding according to clinical or CT assessment. One death occurred by 30 days after admission. Clinical improvements as determined by a decrease in the National Institutes of Health Stroke Scale score were demonstrated at 30 days after treatment in 7 of 9 patients. The rate of hemorrhage lysis was compared between 8 patients who completed treatment, and patient cohorts treated for IVH and ICH using identical doses of rt-PA and catheter drainage but without the ultrasound (courtesy of the MISTIE [Minimally Invasive Surgery plus T-PA for Intracerebral Hemorrhage Evacuation] and CLEAR II [Clot Lysis Evaluating Accelerated Resolution of Intraventricular Hemorrhage II] studies). Compared with the MISTIE and CLEAR data, the authors observed a faster rate of lysis during treatment for IVH and ICH in the patients treated with sonolysis plus rt-PA versus rt-PA alone. CONCLUSIONS: Lysis and drainage of spontaneous ICH and IVH with a reduction in mass effect can be accomplished rapidly and safely through sonothrombolysis using stereotactically delivered drainage and ultrasound catheters via a bur hole. A larger clinical trial with catheters specifically designed for brain blood clot removal is warranted.